Morphometric Analysis of Odontoid in Nepalese Individuals of Eastern Nepal - Jha, Subash Chandra; Raut, Satendra (Journal of College of Medical Sciences-Nepal, 2022)
Introduction There is ethnic variation in the morphometry of odontoid and it is always mandatory to know the anatomy of odontoid before surgery to achieve the success of the surgery either with 1 or 2 screws fixation. There is no literature on the morphometry of odontoids in the Nepalese population. Methods Two hundred and ten consecutive patients whose CT-scan of the head or cervical spine were done without any evidence of cervical injury or fracture were included in the study. Morphometric measurements were done using Horos software in axial, coronal, and sagittal planes. Results The mean age was 42.32 ± 16.16 (range 17-76) years including 104 males and 106 females. The mean screw length was 36.52 ± 3.14 mm and the screw insertion angle in relation to the inferior endplate of C2 vertebrae is 55.66 ± 4.74 degrees. The anteroposterior diameter of the odontoid was significantly more than the transverse diameter at the base and at the waist of the odontoid. A total of 97 (46.1%) individuals had their transverse waist diameter between 7.4 -9 mm and 31 (14.76%) had their dimension below 7.4 mm. Conclusions Almost 2/3rd of the Nepalese population has an inadequate diameter of odontoid for two 3.5 mm screws since the transverse waist diameter is less than 9 mm. Hence, either two 2.7 mm screws or a single 4.5 mm screw fixation should be considered in the majority of the cases but only after preoperative CT-scan-based morphometric measurement.